A review of t-junction geometrical effect on two-phase separation - Saieed, A. (Asian Research Publishing Network, 2016)
T-junctions have been used in piping networks to fuse or split incoming fluids for decades. It is because of their massive utization specially in petroleum industry, that it is the subject of interest for many researchers to this date. In oil and gas sector, T-junctions are usually used as a partial two phase separator. Two-phase separation in a T-junction is a complex phenomena because of its dependence upon many parameters, one of which is the geometrical features of the Tjunction. Here, in this paper the effect of different geometrical features of the T-junction on two-phase separation will be discussed to compile different concepts governing the phase separation in a T-junction. It was felt that further research is required to explore the effects of various inserts and combination of more than one T-junctions on phase separation. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.